WRITING ON THE WALL: INTEGRATING PADLET IN ESP WRITING CLASSROOMS - Suparmi Suparmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Learning to write English on a wall is what a Padlet may look like to those who have used this virtual pinboard. This digital tool is easy to use yet effective for assisting students in learning to write. This study investigated the effectiveness of integrating Padlet on students’ writing skills in English for Specific Purposes (ESP) classrooms. 78 ESP students at a State Islamic University participated in this study. To collect data, pre and post-tests were administered. The data was analyzed using the t-test for independent samples. The results from the pre-post tests showed a significant enhancement in students’ writing skills. The results revealed that the integration of Padlet is effective in improving students’ writing skills in English language learning. Lastly, practical and essential suggestions related to the result of the study are discussed, particularly for future researchers, English language teachers, and ESP students.